Tumor induction by the LTR, v-src, LTR DNA in four B (MHC) congenic lines of chickens - Svoboda, J; Plachý, J; Hejnar, J; Karakoz, I; Guntaka, R V; Geryk, J (Immunogenetics, 1992)
We report that the cloned DNA harboring the long terminal repeat (LTR), v-src, LTR proviral structure is tumorigenic in chickens of the Prague congenic lines. The growth rate of these tumors is by far the highest in the recombinant CC.R1 line, the B haplotype of which is composed of the B-F/L4 and B-G12 subregions originating from different naturally occurring haplotypes. Some of the tumors induced by the LTR, v-src, LTR DNA are repeatedly transplantable in syngeneic chickens, maintain unaltered provirus, and express v-src mRNA. Differences in the response to challenge with Rous sarcoma virus (RSV) and LTR, v-src, LTR DNA on a given experimental model are compared and possible involvement of an interaction between B-F/L and B-G region genes is considered. Regression of the LTR, v-src, LTR DNA-induced tumors did not prevent the formation and growth of tumors induced subsequently by RSV.
Keywords: kur domácí; geny src; Neoplasms; Genes, src; Chickens; Cloning, Molecular; Southernův blotting; klonování DNA; Repetitive Sequences, Nucleic Acid; DNA nádorová; Blotting, Northern; buněčné dělení; viry ptačího sarkomu; DNA, Neoplasm; Avian Sarcoma Viruses; northern blotting; Animals; Cell Division; proviry; zvířata; Genetic Complementation Test; testy genetické komplementace; polymorfismus délky restrikčních fragmentů; repetitivní sekvence nukleových kyselin; nádory; Blotting, Southern; Proviruses; Polymorphism, Restriction Fragment Length